The relationships between work-family conflict and life satisfaction and happiness among nurses: a moderated mediation model of gratitude and self-compassion - El Keshky, Mogeda El Sayed; Sarour, Enas ObaidAllah (Frontiers in Public Health, 2024)
Background Researchers and practitioners are concerned with the impact of work-family conflict on the well-being of workers, including those in the health care sector, and previous research suggested that nurses were experiencing a range of negative outcomes. Aim To investigate the potentially mediating role of self-compassion and moderating role of gratitude in the relationships between work-family conflict and both life satisfaction and happiness among Saudi nurses. Method A cross-sectional survey was conducted with 368 nurses (men age = 35.18, SD = 6.67, 70.65% of females). Nurses were recruited via social media using convenience sampling techniques. They completed the Satisfaction with Life Scale, the Subjective Happiness Scale, the Gratitude Questionnaire–6, the Self-Compassion Scale, and the Work-Family Conflict Scale, as well as a set of demographic questions. The data were analyzed using PROCESS MACRO model 4 and 8, and the reporting followed STROBE checklist. Results As expected, the study found a negative relationship between work-family conflict and both life satisfaction and happiness. These relationships were mediated by self-compassion. For the relationships between work-family conflict and life satisfaction and happiness, and between family-work conflict and happiness, this mediation was moderated by gratitude. Conclusion This study built on positive psychology and demonstrated that the positive personality traits of self-compassion and gratitude can engender enhanced life satisfaction and happiness among Saudi nurses.